Addressing the Economic Impacts of COVID-19: A Gender-Based Training Needs Assessment and Intervention in Barangay Acmac, Iligan City - Sison, Maria Pia; Embornas, Amabelle; Ponce, Sulpecia; Edera, Joana Marie (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study aims to evaluate the gender-based training needs of men and women impacted by COVID-19 in Barangay Acmac, Iligan City. Using Participatory Needs Assessment (PNA), the research allowed 30 men and 30 women to identify their economic challenges and propose solutions. Key findings include: before the pandemic, 78% of respondents were employed full-time, with 80% of men and 76% of women in such roles. Post-pandemic, many transitioned to part-time work, with 43% now working part-time (30% of men and 56% of women). Prior to COVID-19, 73% relied on formal paid work as their main income source. Post-pandemic, income sources diversified, with some retaining formal work (19% of men and 30% of women) and others turning to trading (9%), service businesses (8%), and technical work (6%). A substantial 96% of respondents (29 men and 29 women) reported changes in income sources since March 2020. In addition, men preferred welding training, while women prioritized cookery training. Additional male interests included masonry, automotive servicing, driving, and electrical work, while women showed interest in Food and Beverage Services NC II certification. The study highlights the need for targeted livelihood training to address the economic challenges caused by COVID-19.